Review of Paediatrics Inpatient at a Zonal Hospital - Paudel, Kiran Mani; Sharma, Sindhu (Journal of Nepal Paediatric Society, 2013)
Introduction: Childhood illnesses cause significant number of admissions in different level hospitals. This retrospective study was undertaken to analyze the morbidity pattern in the Paediatric ward at a Zonal Hospital with aim that the results obtained will help in planning, prioritizing and implementing preventive, promotive and curative health care activities of the children in resource poor community. Materials and Methods: This study was carried out retrospectively for one year from July/Aug 2010 – June/July 2011. Age, sex, diagnosis, month of admission, duration of admission and the frequency of diseases were evaluated. Results: A total number of 977 patients were admitted during the study period. There were 579(59%) male and 398(41%) female children. Less than five years age group accounted for 569(58%) excluding the neonates. In the study period, respiratory tract infections were the commonest cause of admission 309(31.6%), gastrointestinal including diarrhoeal diseases were 278(28.5%), enteric fever comprised of 69(7%), and other diseases comprised of about 390(39.5%). Of the total admissions, CNS diseases comprised of 128(13%) of which 29(3%) were meningitis and meningoencephalitis. Sixty seven (52%) of the total CNS cases were due to febrile convulsion. Renal and cardiovascular diseases were 8.5% and 1.5% respectively. Conclusion: Children under five years of age being the most common age group amongst all, with respiratory and gastrointestinal diseases still being the most predominant cause of paediatric morbidity; community level interventions including IMCI should be strengthened for reducing hospital admissions, along with allocation of hospital beds and supplies as per morbidity pattern. DOI: http://dx.doi.org/10.3126/jnps.v32i3.7089 J. Nepal Paediatr. SocVol.32(3) 2012 239-244